Increasing the Capacity of Human Resources and MSME Governance Through the Implementation of Business Continuity Plan in Tambakrejo Village - S Martono; Margareta Rahayuningsih; Sucihatiningsih Dian Wisika Prajanti; Arief Yulianto (Jurnal Abdimas, 2024)
The presto milkfish business activities in Tambakrejo Village are hampered by floods and tidal waves. Floods and tidal waves result in decreased productivity, disruption of the flow of goods and services, and damage to supporting infrastructure. One of the business units affected by the flood and tidal waves is the Enaxmen UMKM managed by Mrs. Kurnia ( Target Partner). Based on information from partners, the disaster that occurred became a serious threat because it greatly disrupted production activities, even at certain times it could not produce because there was no supply of raw materials. The period of 2020-2021 when Covid-19 occurred was a major blow to partners because of the decrease in turnover and production by more than 50% . The problem , based on the conditions above, is that partners are very vulnerable to shocks (disasters) that occur, especially since partners also do not have standard procedures in dealing with these problems . Another problem is that partner marketing is still limited in scope, on the other hand, partners also do not have the capacity to promote products, so that it indirectly has an impact on low product branding. The capacity of Tambakrejo Village MSME actors in managing their business through the implementation of the Business Continuity Plan has increased well . This can be seen from the increasing understanding of MSME actors in planning business continuity amidst the potential for natural disasters . This needs to be done considering that the Tambakrejo Village area is an area that is very prone to flooding, tidal flooding, and fires . MSME actors have also understood online marketing to increase the capacity of the products produced.